Strontium ranelate is a drug to treat osteoarthrosis - Oksana Anatolyevna Nikitinskaya (Современная ревматология)
To prevent disease progression in patients with osteoarthosis (OA) remains a challenging problem. Despite the proposed drug, non-drug, and surgical treatments for OA, there is a clinical need for medications that have a structure-modifying effect and are able to delay or prevent cartilage degradation and to alleviate the clinical manifestations of the disease. A 3-year international randomized clinical trial has demonstrated strong evidence for the symptomand structure-modifying effect of strontium ranelate in female and male patients with clinical primary knee OA. The clinical use of the drug opens up new prospects for preventing the progression of the disease in patients with knee and hip OA.